Intra-thallus variation of phenolic compounds, antioxidant activity, and phenolsulphatase activity in Cystoseira tamariscifolia (Phaeophyceae) from southern Spain - Roberto Teófilo Abdala-Díaz; Alejandro Cabello-Pasini; Eugenia Márquez-Garrido; Felix López-Figueroa (Ciencias Marinas, 2014)
Intra-thallus variation in phenolic content, antioxidant activity, and phenolsulphatase activity (EC 3.1.6.1) was studied in Cystoseira tamariscifolia (Phaeophyceae) from southern Spain. Significant differences in the content of phenolic compounds were found among apical, middle, and basal sections of the thallus of C. tamariscifolia. The concentrations of phenolic compounds and of phenolsulphatase activity were highest in the apical section and decreased toward the basal section. There was a highly significant correlation between the concentration of phenolic compounds and antioxidant and phenolsulphatase activities in C. tamariscifolia. Phenol excretion and phenolsulfatase activity were significantly correlated with integrated irradiance. Cystoseira tamariscifolia grows in tightly packed turfs that promote auto-shading in the middle and basal sections of its thalli, and it is thus likely that the higher polyphenol content in the apical section of this species is a response to the higher exposure to ultraviolet radiation and photosynthetically active radiation relative to the middle and basal sections. These results suggest that this excretion of phenolic compounds might function as a protective mechanism serving as a radiation filter in the immediate surroundings of the C. tamariscifolia thalli.